Plan de exportación de cacao desde el municipio de Pauna Boyacá hacia el mercado New Orleans Estados Unidos (2023)
This project is a research that aims to provide a tool from academia for the company Kakaoteros de Pauna Boyacá in its cocoa internationalization process. For this, a market study was developed in which a search and analysis of data related to the supply and demand of this product is carried out, in order to establish a target country to carry out the export, in addition an analysis and of projection prices, both national and international.